2001
DOI: 10.1038/sj.onc.1204317
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gab proteins in phosphatidylinositol 3-kinase activation by thrombopoietin (Tpo)

Abstract: In this study, we show that upon thrombopoietin (Tpo) stimulation the two adapter proteins Gab1 and Gab2 are strongly tyrosine phosphorylated and associated with Shc, SHP2, PI 3-kinase and Grb2 in mpl-expressing UT7 cells. Although Gab1 and Gab2 seem to mediate overlapping biological signals in many cells, only Gab1 is expressed and phosphorylated in response to Tpo in primary human megakaryocytic progenitors; furthermore, it associates with the same proteins. Although a low level of tyrosine phosphorylated IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 51 publications
(53 reference statements)
2
27
0
Order By: Relevance
“…A novel function of Shc was found to link Gab2 to the phosphotyrosine on the IL-2␤ receptor via Grb2 (41). Consistent with these data, a recent report showed that the Shc docking site on Mpl, Tyr 112 , serves a similar function in promoting Gab phosphorylation by JAK2 (42). However, in our hands, Gab2/SHP2/p85PI3K complex formation was still present in BaF3/T69, albeit reduced compared with BaF3/Mpl cells.…”
Section: Discussionsupporting
confidence: 78%
“…A novel function of Shc was found to link Gab2 to the phosphotyrosine on the IL-2␤ receptor via Grb2 (41). Consistent with these data, a recent report showed that the Shc docking site on Mpl, Tyr 112 , serves a similar function in promoting Gab phosphorylation by JAK2 (42). However, in our hands, Gab2/SHP2/p85PI3K complex formation was still present in BaF3/T69, albeit reduced compared with BaF3/Mpl cells.…”
Section: Discussionsupporting
confidence: 78%
“…Both adipokines induced a strong reduction in insulin receptor substrate 1 expression whereas IL-6 had no effect. Under the same conditions, expression of insulin receptor, Giα2 and insulin receptor substrate 2, another member of the insulin receptor substrate family present in megakaryocytes, 34 was not disturbed. Leptin and resistin receptors induce signaling through the JAK/STAT pathway to expression regulation of suppressor of cytokine signaling (SOCS) proteins, which attenuate cytokine signaling by interfering with receptor function, JAK activity or by targeting activated signaling proteins for degradation by the proteasome.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 75%
“…They are called 'scaffolding' or 'docking' proteins because of the presence of multiple functional motifs mediating interactions with many other signaling molecules (Nishida et al, 1999). Grb2-associated binding proteins are involved in signaling events triggered by a variety of stimuli, including GFs, cytokines, G-coupled receptors and T-and B-lymphocyte antigens, ultimately regulating cell growth, differentiation and transformation (Bouscary et al, 2001;Liu et al, 2001;Sattler et al, 2002). Among the Gab2 direct interactors are proteins with key roles in human cancer when mutated, such as PI3K and the tyrosine phosphatase Ptpn11/Shp2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses have identified signaling molecules that can bind to Gab2 on receptor activation, including the tyrosine phosphatase Ptpn11/Shp2, leading to the activation of Erk and Jnk (Yu et al, 2006), the p85 subunit of PI3K, leading to Akt activation (Bouscary et al, 2001), and Src family kinases (Kong et al, 2003). Therefore, to dissect the signaling pathways downstream of Gab2 that could mediate anchorage-independent growth, we examined the effects on cell vitality of a panel of small molecule inhibitors targeting the abovementioned signaling kinases ( Figure 4a).…”
Section: Gab2-driven Anchorage Independence Requires Src and Involvesmentioning
confidence: 99%